Incidence of a coordinative training program on explosive strength of lower and upper limbs in female cheerleaders aged 12 to 14 years (Impetus, 2022)
Introduction: Currently, the benefits that strength training brings at an early age have been verified, many studies carried out determine a degree of safety regarding this practice as long as it is supervised and adequately dosed, taking into account the individual characteristics of each one, the teaching of the correct execution or technique, is another determining factor in this process, because from this, the risk can be reduced and some type of injury can be prevented. Methodology: After carrying out the pertinent bibliographic review for the development of the investigation, it is determined that it is of an exploratory type, of a mixed approach. The research scope is determined by the number of articles identified at a local (0), regional (0), national (1) and international (14) level, consulted in 5 databases: PubMed, ScienceDirect, Google Academic, G- SE and Sky. Results: The benefits of explosive force training in lower and upper limbs at an early age are verified, because the applied practices and studies determined a degree of safety, and should be adequately supervised and dosed, because from this, it can be reduced the risk and prevention of some type of injury. Conclusions: A continuous process must be followed, because like adults (Fontana, et al., 2004), it determines that the strength levels at these ages also drop considerably, yes, training is stopped, which is why , this ability should be included in the athlete's training plan, because it represents an improvement in their performance.
Keywords: Program; coordination training; explosive strength; cheerleaders